Tips and Tricks to Improve Ergonomics, Efficacy, Versatility, and Overcome Limitations of Micro Percutaneous Nephrolithotomy - Biligere, Sarvajit; Heng, Chin-Tiong; Cracco, Cecilia; Mangat, Reshma; Ong, Chloe Shu-Hui; Thandapani, Karthik; Inoue, Takaaki; Sarica, Kemal; Sabnis, Ravindra B.; Desai, Mahesh; Scoffone, Cesare; Gauhar, Vineet (Frontiers in Surgery, 2021)
Percutaneous Nephrolithotomy (PCNL) has evolved over the decades from Standard to Mini to Ultramini PCNL to Micro-perc, with miniaturisation being the dominant theme and supine approach gaining momentum world over. Micro-perc technique with the all seeing 4.8Fr needle is the least invasive modification of PCNL. Several studies have demonstrated high Stone Free Rates(SFR), lower morbidity, fewer complications and shorter hospital stays. However, its utility has been limited to small volume stones and paediatric urolithiasis due to drawbacks such as high intrarenal pressures in a closed system and the use of only lasers for lithotripsy, hence preventing this novel technique from reaching its full potential. With recent technical advancements in lasers and lasing techniques in retrograde intrarenal surgery (RIRS), there has been a rise in Endoscopic Combined IntraRenal Surgery (ECIRS) as a step ahead in the evolution of percutaneous renal stone management. This has also revived interest in Microperc, and more so in niche cases with diverticular stones, complex renal anatomy, paediatric urolithiasis, elderly population, and anomalous kidneys. We describe how understanding and utilising the construct of the needle system to its fullest potential aids in making micro-perc access versatile, precise and ergonomical, thereby translating to improved outcomes for patients whilst enhancing surgeon experience in PCNL.